2019
DOI: 10.1038/s41598-019-51411-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Neovascular Glaucoma After 25-gauge Vitrectomy for Proliferative Diabetic Retinopathy with Vitreous Hemorrhage: A Retrospective Multicenter Study

Abstract: Neovascular glaucoma (NVG) is a terminal severe complication in eyes with proliferative diabetic retinopathy (PDR), and PDR eyes with vitreous hemorrhage (VH) which undergo vitrectomy may have higher risk of postoperative NVG. The incidence and the prognostic factor of postoperative NVG after 25-gauge vitrectomy with advanced surgical options remain unclear. We retrospectively reviewed medical records of 268 eyes of 268 consecutive PDR patients with VH who underwent 25-gauge vitrectomy and 12 months follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 23 publications
2
25
1
Order By: Relevance
“…There were no significant differences in baseline HbA1c and postoperative NVG between IVI group and non-IVI group. We previously reported that young age, shorter diabetes treatment duration, and higher HbA1c were risk factors of developing postoperative NVG [35]. Liang et al [32] also reported that severe PDR and higher HbA1c were significant prognostic factors of NVG after vitrectomy.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…There were no significant differences in baseline HbA1c and postoperative NVG between IVI group and non-IVI group. We previously reported that young age, shorter diabetes treatment duration, and higher HbA1c were risk factors of developing postoperative NVG [35]. Liang et al [32] also reported that severe PDR and higher HbA1c were significant prognostic factors of NVG after vitrectomy.…”
Section: Discussionmentioning
confidence: 89%
“…Written informed consent was waived by the ethics committees due to the retrospective nature of the study, but all subjects were informed of the study. The study methods were developed in accordance with the relevant guidelines and regulations, and have been reported previously [27][28][29]. Some of the data in this report were also used in other studies [27][28][29].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the risk factor analysis,HbAlc,concomitant diabetic nephropathy(DN) and anti-VEGF therapy were associated with risk of postoperative NVG secondary to PDR.This nomogram suggested that low-level HbAlc(<9%),alleviation of DN and anti-VEGF therapy may be the key individual factors that could reduce the incidence of NVG.In a multicenter study conducted by Takayama and his colleagues [16],younger age, uncontrolled diabetes, no PRP, and postoperative VH were considered to be risk factors for postoperative NVG in PDR patients.Unconsistent with their study,neither age nor preoperative PRP has been screened out as prognostic factors for postoperative NVG in PDR patients.But our study have also found that highlevel HbAlc may indicate the occurrence of postoperative NVG.Microangiopathy caused by uctuations in blood glucose levels has also been reported to contribute to the progression of ischemia [17].Previous publication highlighted that diabetic retinopathy is exacerbated when HbAlc is 6.5% or higher [18],the result of which correlates with our study.So to the best of knowledge,a better control of diabetes mellitus is the key for better prognosis.But a negative correlation between HbAlc and NVG onset was found by Masashi Sakamoto and his colleagues [19],where they ascribed the contradictory result to excessive administration of insulin in patients with NVG and the lack of investigation in the course of diabetic retinopathy.So further studies are still needed to observe the relationship between HbA1c level and NVG onset in PDR patients.…”
Section: Discussionmentioning
confidence: 96%
“…Common complications of vitrectomy for VH due to PDR include corneal epithelial defects, cataract formation, elevated intraocular pressure, neovascular glaucoma (NVG), iatrogenic retinal breaks, recurrent VH, and rhegmatogenous retinal detachment [1,3,4]. Among these complications, recurrent VH is the most common postoperative event, and has been reported in 7-63% of patients [1].…”
Section: Introductionmentioning
confidence: 99%